The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1007/s11663-997-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic thermal decomposition kinetics of SrCO3 by a nonisothermal technique

Abstract: The kinetics of the decomposition of SrCO 3 in argon to SrO and CO 2 were studied in the temperature range 1000 to 1350 K. The thermal decomposition was followed simultaneously by thermogravimetric analysis (TGA) and differential thermal analysis (DTA) during linear heating. By using a nonisothermal method, the complete rate expression was determined from a relatively small number of experimental runs. Shallow beds of fine synthetic powder as well as thin flakes of pressed powder were employed to obtain the ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
6
19
0
1
Order By: Relevance
“…The corresponding weight loss appears in 700-950°C in the TG curves. As reported previously [11], the thermal decomposition of SrCO 3 start at about 1000 K. Therefore the thermal analysis could confirm that the residual SrCO 3 exists in the SrTiO 3 dry gel. However, the endothermic peak disappears by adding PVP into the SrTiO 3 solution.…”
Section: Methodssupporting
confidence: 82%
“…The corresponding weight loss appears in 700-950°C in the TG curves. As reported previously [11], the thermal decomposition of SrCO 3 start at about 1000 K. Therefore the thermal analysis could confirm that the residual SrCO 3 exists in the SrTiO 3 dry gel. However, the endothermic peak disappears by adding PVP into the SrTiO 3 solution.…”
Section: Methodssupporting
confidence: 82%
“…Moreover, it is known that alkaline earth carbonates do not suffer from any weight change below 500°C [43,44]. Thus, it is plausible to relate the observed WL at 230-400°C range to the acetate group decomposition.…”
Section: Thermal Analysesmentioning
confidence: 94%
“…The first peak (being located at 699, 764, and 749°C for CaCo, SrCo, and BaCo mixtures, respectively) can be correlated with the decomposition of the alkaline earth carbonates. Previous studies have identified that CaCO 3 , SrCO 3 , and BaCO 3 undergo decomposition at temperatures higher than 650 [45], 730 [43], and 970°C [44,46], respectively. Knowing that the addition of some oxides like TiO 2 [44] and Cr 2 O 3 [46] shifts the decomposition temperature of BaCO 3 to temperatures as low as 600°C, one may arrive at the conclusion that the presence of Co 3 O 4 also enhances the decomposition temperature of BaCO 3 as well as the other alkaline earth carbonates towards lower temperatures.…”
Section: Thermal Analysesmentioning
confidence: 99%
“…Al aplicar ln a la Ecuación 1 nos queda: [3] Graficando ln k contra 1/T para cada temperatura se puede realizar una regresión lineal entre los puntos cuyo valor de la pendiente (m) es equivalente a -E a /R (Ecuación de la recta).…”
Section: Interpretación De Resultadosunclassified